Effect of Feeding Rice Distillers Dried Grains and Mixture of Non-legume and Legume Straw on Hemato-Biochemical and Mineral Profile of Growing Dairy Heifers - Pandey, Manish; Shah, S.V.; Trivedi, M.M.; Pathan, M.M.; Lunagariya, P.M.; Patel, Y.G. (Indian Journal of Animal Nutrition, 2022)
Under scarcity of livestock feeds and fodder, an investigation on alternate, conventional and nonconventional feed resources is essential. The present study was planned on crossbred heifers (HF×Kankrej) with average body weight of 116.1±4.74 kg for twelve fortnights to study the effect of feeding rice DDGS and a combination of straw (wheat + groundnut) on their hemato-biochemical and mineral profile. Blood samples for hemato-biochemical and mineral profile analysis were collected from heifers at the start of the experiment and thereafter at every fortnightly interval from the jugular vein in the sterilized blood collecting tubes (with and without anticoagulant). Auto-hematology-analyzer Mindray (BC- 2800Vet) and Mindray BS-120 chemistry analyzer were used for hematology and serum biochemistry analysis, respectively. The RBC counts, Hb, PCV%, MCHC, Platelet count, MPV, WBCs and Granulocytes changed significantly (P<0.05) on feeding DDGS though their values were within normal physiological range. On feeding mixture of straw, platelets count and granulocytes changed significantly (P<0.05) but their values were also within normal physiological range. On inclusion of Rice DDGS, serum total protein, urea and phosphorus and on feeding mixture of straw serum glucose, albumin, urea and phosphorus values differ significantly (P<0.05). The serum total protein, glucose, albumin and urea values were within normal physiological interval on feeding DDGS or mixture of straw except phosphorus values (8.77-9.33 mg/dL) which was higher than normal range in all treatment groups irrespective of treatment. The results showed that rice DDGS in concentrate up to 40% and feeding a mixture of groundnut straw and cereal straw (1:1) did not adversely affect the hematology, blood biochemical parameters and mineral profile, all parameters were within normal physiological values except serum phosphorus which was higher than the normal physiological values.